Synthesis and Crystal Structure of 4,4’-Dimethyl-1,1’-[butane-1,4-diyldioxy)bis(nitrilomethylidyne)]dibenzene - Dong, Wen-Kui; Zhang, Yang; Wang, Zheng-Kun; Sun, Yin-Xia; Liu, Peng-Fei (Asian Journal of Chemistry, 2013)
A new bisoxime compound, 4,4'-dimethyl-1,1'-[butane-1,4-diyldioxy)bis(nitrilomethylidyne)]dibenzene, has been synthesized and characterized structurally. There is a crystallographic twofold rotation axis passing through the middle point of the -CH2-CH2-CH2-CH2- linkage. The molecule adopts a trans-conguration with respect to the methylidene unit. There are no intramolecular and intermolecular hydrogen bonds. The two phenyl rings in each molecule are parallel to each other with a perpendicular interplanar spacing of ca. 1.266(3) Å.